Hubungan Gullibility dengan Bandwagon Effect pada Trader Binary Option - Rika Eliana; Ruth Ayala Anggiena (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to examine the relationship between gullibility and the bandwagon effect among binary option traders. Gullibility is defined as an individual's tendency to trust others excessively, even in the presence of cues suggesting dishonesty. Highly gullible individuals are more likely to follow group decisions without critical verification, making them susceptible to the bandwagon effect—a phenomenon in which people adopt behaviors simply because many others are doing the same. This research employed a quantitative correlational approach with 125 participants who were active binary option traders. Data were collected using validated gullibility and bandwagon effect scales. The results revealed a significant positive correlation between gullibility and the bandwagon effect (r = 0.520; p < 0.001). These findings indicate that the higher an individual's gullibility, the greater their tendency to be influenced by the bandwagon effect in trading decision-making.